Y = -4x + 2
Y = -4x - 2
Y = 4x - 2
Y = 4x + 2
Y = 2x + 9
Y = 2x - 9
Y = 2x - 3
Y = 2x + 3
M = -3; b = -6
M = 3; b = -6
M = -6; b = 3
M = 6; b = -3
Y = (1/2)x - 2
Y = (1/2)x - 4
Y = (1/2)x + 4
Y = (1/2)x
Y-3 = 4(x-5)
Y+3 = 4(x+5)
Y-5 = 4(x-3)
Y+5 = 4(x+3)
Y = 4x + 2
Y = (1/4)x + 2
Y = (-1/4)x + 2
Y = -4x + 2
Y = 4x + 13
Y = (-1/4)x + (1/4)
Y = 4x - 11
Y = (-1/4)x + (7/4)
Y = (1/3)x - 3
Y = 3x - 3
Y = (-1/3)x - 3
Y = -3x - 3
F(x) = (1/3)x + 1
F(x) = 3x + 1
F(x) = (1/3)x - 3
F(x) = 3x - 3
Graph shifts down 2
Graph shifts up 2
Graph becomes steeper
Graph becomes less steep
H(x) = 5x + 3
H(x) = -5x + 3
H(x) = -5x - 3
H(x) = 5x - 3
Y = 5x - 22
Y = 5x - 2
Y = 5x + 4
Y = 5x + 14
Slope: -2/3; y-intercept: 2
Slope: -2/3; y-intercept: 3
Slope: 2/3; y-intercept: 2
Slope: 2/3; y-intercept: 3
Y - 5 = (-1/3)(x - 0)
Y - 4 = (-3)(x + 3)
Y - 0 = (1/3)(x - 5)
Y + 3 = 3(x - 4)
I
II
III
IV
Y = (-1/2)x - 5
Y = (-1/2)x - 3
Y = 2x - 3
Y = 2x - 20
Slope: 4; y-intercept: 3
Slope: 4; y-intercept: 4
Slope: (-1/4); y-intercept: 3
Slope: (-1/4); y-intercept: 4
A reflection across the y-axis
A reflection across the y-axis and a translation 4 units up
A rotation (less steep) about (0,2)
A translation up 4 units